Evaluation of a human iPSC-derived BBB model for repeated dose toxicity testing with cyclosporine A as model compound. (June 2021) - Wellens, Sara; Dehouck, Lucie; Chandrasekaran, Vidya; Singh, Pranika; Loiola, Rodrigo Azevedo; Sevin, Emmanuel; Exner, Thomas; Jennings, Paul; Gosselet, Fabien; Culot, Maxime
Abstract: The blood-brain barrier (BBB) is a highly restrictive barrier that preserves central nervous system homeostasis and ensures optimal brain functioning. Using BBB cell assays makes it possible to investigate whether a compound is likely to compromise BBBs functionality, thereby probably resulting in neurotoxicity. Recently, several protocols to obtain human brain-like endothelial cells (BLECs) from induced pluripotent stem cells (iPSCs) have been reported. Within the framework of the European MSCA-ITN in3 project, we explored the possibility to use an iPSC-derived BBB model to assess the effects of repeated dose treatment with chemicals, using Cyclosporine A (CsA) as a model compound. The BLECs were found to exhibit important BBB characteristics up to 15 days after the end of the differentiation and could be used to assess the effects of repeated dose treatment. Although BLECs were still undergoing transcriptional changes over time, a targeted transcriptome analysis (TempO-Seq) indicated a time and concentration dependent activation of ATF4, XBP1, Nrf2 and p53 stress response pathways under CsA treatment. Taken together, these results demonstrate that this iPSC-derived BBB model and iPSC-derived models in general hold great potential to study the effects of repeated dose exposure with chemicals, allowing personalized and patient-specific studies in the future. Highlights: Human stem cell-based blood-brain barrier model for repeated-dose toxicity testing. Barrier tightness and efflux transporter activity over 15 days. Targeted transcriptomic analysis of Cyclosporine A treatment effects. Time-dependent activation of stress response pathways by Cyclosporine A. Concentration-dependent activation of stress response pathways by Cyclosporine A.